2015
DOI: 10.1017/s104795111500181x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in adolescents and young adults with CHD is not reduced: a systematic review and meta-analysis

Abstract: For the first time in a meta-analysis, we have shown that quality of life in adolescents and young adults with CHD is not reduced when compared with age-matched controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 48 publications
1
28
2
Order By: Relevance
“…The results highlight that even after surgical intervention, children and young adult patients with complex CHD had worse cardiac-related HRQOL compared with those with moderate and mild CHD. The review also provides an update to existing reviews on general HRQOL, important in this rapidly changing field 9. The findings demonstrate that postoperative patients with CHD have worse overall and domain-specific HRQOL than their age-matched healthy controls.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The results highlight that even after surgical intervention, children and young adult patients with complex CHD had worse cardiac-related HRQOL compared with those with moderate and mild CHD. The review also provides an update to existing reviews on general HRQOL, important in this rapidly changing field 9. The findings demonstrate that postoperative patients with CHD have worse overall and domain-specific HRQOL than their age-matched healthy controls.…”
Section: Discussionmentioning
confidence: 95%
“…Several meta-analyses on HRQOL for patients with CHD have identified worse cognitive functioning and more distress postoperatively in children and adolescents,8 and worse physical functioning in adolescents9 and adults,10 particularly in complex CHD. However, inconsistencies are present, with one meta-analysis indicating no difference in HRQOL for people with CHD and their age-matched controls 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first meta‐analysis on QoL in CHD was published in 2015 . Schroder et al included studies on adolescents or young adults with mild, moderate or complex CHD and reported QoL as a single index score.…”
Section: Introductionmentioning
confidence: 99%
“…With the majority of patients born with congenital heart disease (CHD) nowadays surviving into adulthood [1,2], there has been increasing interest in the study of quality of life (QOL) in adults with congenital heart disease (ACHD) [3,4]. An initial QOL study in Maltese ACHD patients used vitality and mental health questionnaires from the 36-item short-form health survey (SF-36), which had previously been applied to the general Maltese population during the 2008 European Health Interview Survey [5].…”
Section: Introductionmentioning
confidence: 99%